1653 How Do Trainees Prepare for Operating and Improve Theatre Learning Experiences?. (12th October 2021) - Dunstan, M; Fawns, T
Abstract: Introduction: Reforms to surgical training in the last three decades have threatened to reduce trainees' operative experience. In 2012 ASiT recommended that trainees "take a proactive role in utilising all training opportunities" and that they "should be well prepared". Published quantitative studies into surgical preparation involve mental practice and simulation and make assumptions that these are the most appropriate preparatory techniques. No qualitative studies have been published that explore how trainees prepare, to put this evidence base in context. This study aimed to investigate what trainees do to prepare for operating, their opinions on preparation for surgery, and how preparation may improve training experiences. Method: Twelve General Surgical trainees consented to semi-structured interviews at a London District General Hospital. Interviews were recorded, transcribed and thematic analysis was undertaken. Results: Interviewees described how preparation involves complex interactions between learning resources, their mental processes, emotions, the actions, and attitudes of other members of the theatre team, and situational and organisational barriers. These affected the quality of preparation and training experiences. Significant barriers to preparation were identified as a lack of learning resources and time to prepare. Techniques for preparation were mainly learnt informally through the 'hidden curriculum' and were lacking from the formal curriculum. Trainees felt that raising awareness of preparatory processes may enhance learning experiences. Conclusions: An awareness of the factors that affect preparation and actions to mitigate barriers to preparation may help trainees to gain more from training opportunities, in the context of threats to training and the Covid-19 pandemic.